Seasonal and Regional Variations in Chronic Obstructive Pulmonary Disease Exacerbation Rates in Adults without Cardiovascular Risk Factors - So, Jennifer Y.; Zhao, Huaqing; Voelker, Helen; Reed, Robert M.; Sin, Donald; Marchetti, Nathaniel; Criner, Gerard J. (Annals of the American Thoracic Society, 2018)
Colder temperatures have been shown to increase hospitalization and mortality rates in adults with chronic obstructive pulmonary disease (COPD) and cardiac disease. Seasonal influences on exacerbation rates in adults with severe COPD but without significant cardiovascular disease are unclear. In addition, regional variations in COPD exacerbations in North America have not yet been explored. In this study, we sought to determine the seasonal and regional variability in exacerbation rates in those with COPD but without significant cardiovascular risk factors. We studied adults without cardiovascular risk factors from STATCOPE (Simvastatin in the Prevention of COPD Exacerbations) and placebo arm of MACRO (Azithromycin for the Prevention of Exacerbations of COPD) studies. Forty-five study sites were divided into climate regions in Canada and the United States; seasons were defined as winter, spring, summer, and fall. The primary outcome was the rate of COPD exacerbation. Secondary outcomes included time to first exacerbation, severity of exacerbations, all-cause mortality, and antibiotic and steroid use. We analyzed 1,175 subjects with a mean age of 63.3 ± 8.6 years, forced expiratory volume in 1 second of 41.5 ± 17.1% predicted, and 53.6 ± 29.4 pack-years of smoking history. The COPD exacerbation rate was higher in winter (0.13 exacerbations/person-month) than in spring, summer, and fall (0.11, 0.079, and 0.10 exacerbations/person-month, respectively) (P < 0.001). Summer had the highest proportion of severe exacerbations (40.5%) compared with spring, fall, and winter (32.6%, 34.7%, and 33.1%, respectively) (P = 0.004). Mortality was highest in spring and winter (34% and 30%, respectively). There was significant regional variability in the time to first exacerbation, with the Southeast and West having longer median times to first exacerbation (350 and 342 d, respectively, compared with 184 d in other regions) (P < 0.001). Significant seasonal and regional variability exist in the rate and severity of exacerbations and overall mortality in adults with COPD without cardiovascular disease.